Mannan‐binding lectin promotes keratinocyte to produce CXCL1 and enhances neutrophil infiltration at the early stages of psoriasis. Issue 9 (13th August 2019) - Zeng, Jiaqi; Chen, Xi; Lei, Ke; Wang, Di; Lin, Lin; Wang, Yajie; Li, Yao; Liu, Yunzhi; Zhang, Liyun; Zuo, Daming; Sun, Ledong
Abstract: Psoriasis is a chronic, relapsing inflammatory skin disorder. Numerous experimental evidence and therapeutic evidence have shown that the innate immune response is critical for the pathogenesis and development of psoriasis. Mannan‐binding lectin (MBL), a prototypic pattern recognition molecule of the innate immune system, plays an essential role in the host defense against certain infections and also appears to be a major regulator of inflammation. In this study, we investigated the function of MBL on the course of experimental murine imiquimod (IMQ)‐induced psoriasis. Our data showed that MBL‐deficient (MBL −/− ) mice exhibited attenuated skin damage characterized by greatly decreased erythema compared with wild‐type control mice during the early stages of IMQ‐induced psoriasis‐like skin inflammation. The reduced skin inflammation in MBL −/− mice was associated with the decreased infiltration of neutrophils. Furthermore, we have determined that MBL deficiency limited the chemokine CXCL1 production from skin keratinocytes upon IMQ stimulation, which might be responsible for the impaired skin recruitment of neutrophils. Additionally, we have provided the data that MBL protein promotes the IMQ‐induced expression of CXCL1 and activation of MAPK/NF‐κB signalling pathway in human keratinocyte HaCaT cells in vitro. In summary, our study revealed an unexpected role of MBL on keratinocyte function in skin, thus offering a new insight into the pathogenic mechanisms of psoriasis.